2018
DOI: 10.1002/mc.22814
|View full text |Cite
|
Sign up to set email alerts
|

Peptidyl‐prolyl cis/trans isomerase Pin1 regulates withaferin A‐mediated cell cycle arrest in human breast cancer cells

Abstract: We have reported previously that withaferin A (WA) prevents breast cancer development in mouse mammary tumor virus-neu (MMTV-neu) transgenic mice, but the mechanism is not fully understood. Unbiased proteomics of the mammary tumors from control- and WA-treated MMTV-neu mice revealed downregulation of peptidyl-prolyl cis/trans isomerase (Pin1) protein by WA administration. The present study extends these findings to elucidate the role of Pin1 in cancer chemopreventive mechanisms of WA. The mammary tumor level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Breast cancer ranks first in the common malignant tumors in women, the current incidence of which accounts for more than 10% of the systemic tumors and seriously affects the physical health of women 19 Breast cancer occurs frequently in postmenopausal women mainly at the age of 45-65 years. With the environmental deterioration and other factors, a younger trend of breast cancer occurrence has been shown in recent years 20 The radical surgical resection, combined with radiotherapy and chemotherapy, marks the improvement regarding the survival time of early breast cancer patients, but its therapeutic effect is not satisfactory on advanced breast cancer patients 21 miRNA, as a kind of endogenous small noncoding RNA, plays an important role in cell differentiation, proliferation, and apoptosis through regulating the signaling pathway. Accumulative evidences indicate that a variety of miRNAs are involved in the regulation process of several tumors and play similar roles to tumor suppressor genes and oncogenes 22,23 The abnormal expressions of miR-21 and miR-205 are possibly related to the occurrence and development of breast cancer 12 Li et al 24 found that the miR-205 expression level is increased in epithelial ovarian cancer, and is closely related to the proliferation and invasion of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer ranks first in the common malignant tumors in women, the current incidence of which accounts for more than 10% of the systemic tumors and seriously affects the physical health of women 19 Breast cancer occurs frequently in postmenopausal women mainly at the age of 45-65 years. With the environmental deterioration and other factors, a younger trend of breast cancer occurrence has been shown in recent years 20 The radical surgical resection, combined with radiotherapy and chemotherapy, marks the improvement regarding the survival time of early breast cancer patients, but its therapeutic effect is not satisfactory on advanced breast cancer patients 21 miRNA, as a kind of endogenous small noncoding RNA, plays an important role in cell differentiation, proliferation, and apoptosis through regulating the signaling pathway. Accumulative evidences indicate that a variety of miRNAs are involved in the regulation process of several tumors and play similar roles to tumor suppressor genes and oncogenes 22,23 The abnormal expressions of miR-21 and miR-205 are possibly related to the occurrence and development of breast cancer 12 Li et al 24 found that the miR-205 expression level is increased in epithelial ovarian cancer, and is closely related to the proliferation and invasion of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With the environmental deterioration and other factors, a younger trend of breast cancer occurrence has been shown in recent years20 The radical surgical resection, combined with radiotherapy and chemotherapy, marks the improvement regarding the survival time of early breast cancer patients, but its therapeutic effect is not satisfactory on advanced breast cancer patients 21 miRNA, as a kind of endogenous small noncoding RNA, plays an important role in cell differentiation, proliferation, and apoptosis through regulating the signaling pathway. With the environmental deterioration and other factors, a younger trend of breast cancer occurrence has been shown in recent years20 The radical surgical resection, combined with radiotherapy and chemotherapy, marks the improvement regarding the survival time of early breast cancer patients, but its therapeutic effect is not satisfactory on advanced breast cancer patients 21 miRNA, as a kind of endogenous small noncoding RNA, plays an important role in cell differentiation, proliferation, and apoptosis through regulating the signaling pathway.…”
mentioning
confidence: 99%
“…WFA exhibits therapeutic potential against cardiac ischemia reperfusion injury [20]. WFA has been shown to inhibit growth and induce apoptosis in colon cancer [21], colorectal cancer [22], breast cancer [23], and oral cancer [24]. Acting as a potential c-Met inhibitor, WFA inhibits stemness in pancreatic cancer [25] and also inhibits epithelial-mesenchymal transition in non-small cell lung cancer cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, covalent modification of cysteine‐303 residue in β‐tubulin was implicated in mitotic arrest resulting from WA exposure . As WA is an electrophile, covalent modification of other proteins has also been documented including vimentin and peptidyl‐prolyl cis / trans isomerase Pin1 . The WA‐induced apoptotic cell death in human breast cancer cell lines was associated with the production of reactive oxygen species and accompanied by induction/activation of Bax and Bak proteins .…”
Section: Introductionmentioning
confidence: 99%
“…13 As WA is an electrophile, 13 covalent modification of other proteins has also been documented including vimentin and peptidyl-prolyl cis/trans isomerase Pin1. [16][17][18] The WA-induced apoptotic cell death in human breast cancer cell lines was associated with the production of reactive oxygen species and accompanied by induction/activation of Bax and Bak proteins. 9 The induction of Bak protein expression was also observed in vivo in chemically induced mammary tumors from WA-treated rats in comparison with controls.…”
mentioning
confidence: 99%